How Social Media Marketing and Brand Image Shape College Decision-Making Through Perceived Value - Ella Manisa Br Karo; Syahputra Syahputra; Putu Nina Madiawati (AIBPM Publisher, 2025)
The growing influence of digital platforms has transformed marketing practices in higher education, with social media emerging as a key channel in shaping students’ enrollment decisions. This study aims to examine the effect of social media marketing and brand image on college decision-making, with perceived value serving as a mediating variable. A quantitative approach using Partial Least Squares Structural Equation Modeling (PLS-SEM) was applied to analyze data from 461 respondents. The results reveal that social media marketing significantly influences college decision both directly (? = 0.668, p 0.001) and indirectly through perceived value (? = 0.059, p = 0.013). Brand image also impacts college decision directly (? = 0.105, p = 0.031) and indirectly via perceived value (? = 0.032, p = 0.039). The model explains 69.1% of the variance in college decision (R² = 0.691). These findings highlight the importance of digital branding in enhancing students’ perceived value and influencing enrollment behavior. The study contributes to the literature on student decision-making and offers strategic insights for universities to optimize their digital engagement and institutional image.